Uber structure's managerial algorithmic communication and drivers' health issues: sensemaking of work strategic resistance - El Bourkadi, Salma (Frontiers in Communication, 2023)
This article focuses on the role algorithms play as a communicative infrastructure that contributes to poorer occupational health in the gig economy by interviewing fifty Uber drivers based on the life-story methodological approach. Specifically, the paper draws attention to Uber's managerial algorithmic communication and its effects on drivers' occupational health by engaging with Giddens' theoretical framework of structure-agency and Weick's theory of sensemaking. Further, the study also explored the drivers' different factors contributing to the construction of individual and collective resistance to Uber's monopoly. The findings revealed that Uber's structure imprisons the users' freedom of negotiation and action which creates a stressful work environment as managerial algorithmic communication only function effectively in ideal working conditions while abnormality is very frequent in a profession like transportation. Drivers' agency consists of organizing individual and collective resistance to change Uber's work decision and weaken it. On and outside platform resistance strategies are deployed by drivers to pressure Uber with the goal of protecting their occupational health.